Experimental study on dynamic characteristics and energy dissipation of weakly cemented rock-like materials - Shi, Guodong; Yao, Duoxi; Wu, Jiehao; Meng, Fangyi (Frontiers in Materials, 2025)
The structural stability of coal seam roof rock mass under dynamic load in engineering practice is directly influenced by the dynamic characteristics of weakly consolidated coal measures rock. A study was conducted on two types of rocks, mudstone and siltstone, around the roof of coal seam No. 31 in Renlou Coal Mine, northern Anhui Province. Rock-like specimens were created using similar materials for analysis. The mechanical properties, energy dissipation characteristics, and fractal characteristics of these rocks were investigated using a 75 mm Split Hopkinson Pressure Bar (SHPB) test system at five different impact velocities. The findings are as follows: 1) As the impact velocity increases, the strain rate of the rock linearly increases while the dynamic uniaxial compressive strength exponentially increases. 2) With an increase in strain rate, there is a negative correlation between rock fragmentation and a positive correlation with the number of fragments produced; additionally, the fractal dimension shows an increasing quadratic term function relationship. 3) There exists a linear positive correlation between incident energy and impact velocity; moreover, as incident energy increases, so does the amount of energy lost due to rock breakage. These research results provide both theoretical and experimental foundations for mine dynamic disaster protection.